The Relationship Between Parents' Knowledge, Healthy Behaviors and The Incidence of Influenza in Pre-School Children - Amirah Syafiqah Zahra; Nurul Aziza; Dian Utama Pratiwi Putri (Universitas Ibn Khaldun Bogor, 2026)
Background: Influenza is an acute respiratory tract infection with a high transmission rate, particularly among preschool-aged children whose immune systems are not yet fully developed. In the working area of the Kota Agung Health Center, Tanggamus Regency, influenza has been the most prevalent disease in the last three years, with an increasing trend from 2,850 cases in 2021 to 3,142 cases in 2023. This study aimed to analyze the relationship between parental knowledge and healthy behavior with the incidence of influenza in preschool-aged children in 2025. This study employed a quantitative research design with a cross-sectional approach. The study population consisted of 947 parents, with a sample of 273 respondents determined using the Lemeshow formula. Data were collected through a structured questionnaire tested for validity and reliability. Univariate and bivariate analyses were performed, with the chi-square test applied at a 95% confidence level (α = 0.05). The findings revealed a significant relationship between parental knowledge and the incidence of influenza in preschool-aged children (p = 0.001). Similarly, parental healthy behavior was significantly associated with influenza incidence (p = 0.002). Conclusion: This study demonstrates that parental knowledge and healthy behavior are important determinants in reducing the risk of influenza among preschool-aged children. Strengthening health education, promoting healthy lifestyles, and implementing continuous health promotion programs in the community are crucial strategies to prevent influenza and its complications.